Teacher's interaction styles during sociodramatic play that promote reading and writing among preschoolers - Tongson, Excelsa C. (2014)
This study was conducted to help understand a teacher’s facilitation of reading and writing during sociodramatic play among Filipino preschoolers. It describes how Filipino preschool teachers demonstrate redirecting and extending style interactions as they participate during sociodramatic play. It also identifies the ways by which the teacher provided print-rich environments in the dramatic play area to promote early reading and writing among Filipino children with ages ranging from four years old to five years old and 11 months. Five female teachers from four schools in Quezon City that adopt the play curriculum based on a set of criteria were studied. Each teacher was interviewed regarding play, her role, and how she prepares the dramatic play area. She was observed for 10 consecutive school days. The teachers’ interaction styles were classified as either extending or redirecting. Four of the f ive teachers demonstrated at varying degrees both extending and redirecting styles as they participated in the children’s sociodramatic play. The interaction style of the teacher revealed her ability to perform within the context of the play and the ways she assisted children in performing reading and writing activities. The considerable increase in the frequency of children’s literacy activities during sociodramatic play could be attributed to the combination of extending style interaction and the integration of literacy materials in the dramatic play area.
Keywords: Reading (Preschool); Writing -- Study and teaching (Preschool); Drama in education; Preschool education; Teaching methods